STRATEGI PEMBELAJARAN BISIK -BISIK PERBANKAN CERIA DALAM IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR DASAR PERBANKAN PADA KELAS X AKUTANSI SMK NEGERI 1 RANGKASBITUNG - Eti Sumiati (Universitas Sultan Ageng Tirtayasa, 2022)
Fundamentals of banking work well so it requires a fun learning method for students. The conventional learning method is by way of teacher-centered lectures so that students become bored and unmotivated and not motivated to master the material, so the teacher must be able to choose a fun learning method. The method in this research is CAR (Classroom Action Research) with data sources for students of class X Accounting 3 SMKN 1 Rangakasbitung. The results of the research on the activity of cycle 1 students doing group assignments were quite good, however, the activities of students asking and answering questions were still not enthusiastic about doing the activity, only 22%, this point still needed improvement. Student activities in discussing in groups reached 91% and students who pay attention to the teacher's explanation reached 86%. Looking at the presentation of students' practical (psychomotor) observations, it turns out that cycle 2 shows that: students doing assignments and discussing in groups are quite good at 90.90%, students who pay attention to teacher explanations are 93.81%, activities carrying out tasks are quite good get 100% , students who pay attention to students' presentations 90.90%. However, students who want to ask and answer questions are still 54.54%. From all of these activities, students are used to and are no longer awkward in doing learning activities with the whisper-whisper strategy of cheerful banking.